KUALITAS PELAYANAN PASIEN BADAN PENYELENGGARA JAMINAN SOSIAL DI PUSAT KESEHATAN MASYARAKAT BIROMARU KABUPATEN SIGI - Susanti Susanti (Katalogis, 2016)
This study aimed to analyze the quality of service (Tangibles Reliability, Responsiveness, Assurance and Empathy) patients at the health center BPJS Biromaru Sigi. This type of research is to use Approach Method Qualitative Research aimed at providing a general overview of the ministry of Health BPJS Askes card holders in PHC Biromaru Sigi. Determination of informants in a qualitative study based on existing characteristics, therefore, the informant was an employee who provides services in primary health and community participants Biromatu BPJS Askes card holder, determination technique informant done purposively. The findings of the research showed that overall health service users in this patient BPJS cardholder Biromaru Askes in the health center can be said that the service provided is good but not fully in accordance with the expectations of society BPJS participants Askes card holder. Still need to make improvements such as a doctor who is still too late to come to the health center and the availability of drugs that are sometimes needed no medication in the health center. Good service at health centers and the lack of distance between communities and health workers so that they utilize health services at the health center Biromaru.